Novel lignin as natural-biodegradable binder for various sectors-A review - Mili, Medha; Hashmi, Sayed Azhar Rasheed; Ather, Madeeha; Hada, Vaishnavi; Markandeya, Nishant; Kamble, Sanjay; Mohapatra, Mamata; Rathore, Sanjai Kumar Singh; Srivastava, Avanish Kumar; Verma, Sarika (Journal of Applied Polymer Science, 2022)
Lignin functions as an essential polymer in plants that forms the plant body's structural framework. The natural glue holds the cellulosic fibers together in the plant body, thereby providing rigidity and strength. Despite this, lignin shows promising relevance for biomaterial production due to its abundance, nontoxic nature and biodegradability. Considerably, adhesive components were derived from petroleum, which is increasingly more expensive. Hence, lignin, the natural glue in plant materials, gained much popularity because of its phenolic nature, making it an attractive substitute for adhesives. Lignin-based binders are produced through phenols substitution in phenol-formaldehyde resins with lignin due to their similar structural framework. Many researchers have confirmed the multifunctional applications of lignin, such as wood adhesive in fiber board, plywood and particleboard, a binder in printed wiring boards, abrasive tools, epoxy asphalts, epoxy wood composites, 3D printing, adhesive hydrogels, soil suppressants, lignocellulosic paper and coatings. This review presents a comprehensive description of the utilization of lignin-based binders for different applications. The present work highlights the discussion on the various methods by which lignin can be used to replace synthetic binders. This review focuses on global research work introducing lignin in different chemical adhesives for a more cost-effective and less harmful alternative.
Keywords: binder; biodegradable; lignin; multifunctional

Efficient continuous catalytic process for production of bisphenol A - Dhotre, Kapil; Patil, Chetana Rupak; Tarade, Komal P.; Markandeya, Nishant; Pathak, Abhishek; Bhongale, Sunil S.; Kamble, Sanjay P. (Organic Process Research & Development, 2025)
Bisphenol A (BPA) is a versatile chemical compound that is essential for producing durable polycarbonate plastics and strong epoxy resins, which are integral to numerous everyday products. In the present study, BPA was prepared using phenol and acetone using a highly active and reusable ion-exchange resin (IER) Lewatit K1131S as the catalyst. Under optimized conditions, an acetone conversion of 84% and a BPA selectivity of 94% were achieved. The produced BPA was further purified, resulting in a 96% isolated yield with 99.5% purity. The reusability of Lewatit K1131S has been studied, and it was found that it can be reused multiple times without affecting the selectivity for BPA. The kinetics of the reaction was studied using the Langmuir-Hinshelwood model; it was found that the reaction follows pseudo-first-order kinetics, and the apparent activation energy was determined to be 12.7 kJ/mol. A continuous pilot scale process for the production of BPA using a fixed-bed reactor (packed with ion-exchange resin) has been developed. Pilot plant trials were conducted at different flow rates such as 200, 300, and 500 g/h, and a downstream processing methodology using an agitated thin film evaporator (ATFE) was employed for the BPA purification. This resulted in high throughput, producing 99.2% isolated BPA yield with 99.5% HPLC purity. Additionally, the robustness and viability of the catalyst were assessed at a flow rate of 200 g/h, producing 22.5 kg of BPA per kg of catalyst, highlighting its cost-effectiveness, stability, and resistance to deactivation, which shows its suitability for industrial-scale applications. The environmental viability of the process was further evaluated by using the E-factor and Process Mass Intensity (PMI) metrics. The estimated E-factor was 0.3118, while the corresponding PMI was 1.3935. These lower values indicate reduced waste generation, improved material efficiency, and enhanced sustainability of the process.
Keywords: bisphenolA; BPA purification; Continuous process; E-factor; ion-exchange resins (IER); PMI; process optimization; reactionkinetics

Highly efficient, co-solvent assisted glycolytic depolymerization of waste polyethylene terephthalate (PET) into Bis(2-hydroxyethyl) terephthalate (BHET) monomer - Markandeya, Nishant; Solanki, Bhanupratap Singh; Ramalingam, Karthick; Kamble, Sanjay (Industrial & Engineering Chemistry Research, 2025)
Recently, growing use of plastics has led to the accumulation of waste that must be dealt with paramount priority. Among all plastic wastes, polyethylene terephthalate (PET) is the most widely used thermoplastic polyester globally because of its extensive applications in packaging, automotive manufacturing, and textile markets. Thus, there is a need to develop a sustainable and viable PET recycling process. This study presents an efficient solvothermal process for the depolymerization of PET into bis(2-hydroxyethyl) terephthalate (BHET) using co-solvent assisted glycolysis. The process uses N-methylimidazole (NMI) as a cosolvent with ethylene glycol (EG), achieving complete PET conversion and 92% BHET yield under optimized reaction conditions (180 degrees C, 45 min, PET:EG:NMI ratio of 1:7:8) without using a catalyst. The effectiveness of the cosolvent system was attributed to its polarity and H-bonding capabilities, which enhanced polymer swelling and facilitated the depolymerization. SEM analysis revealed pore formation in the NMI-treated PET, whereas FTIR studies confirmed the progressive formation of ester groups during depolymerization of PET. Kinetics studies based on different models indicated that, at higher temperatures, the surface reaction and homogeneous model proved to be rate-controlling due to the elimination of mass transfer limitations. A preliminary technoeconomic analysis and recyclability experiments further supported the scalability potential of the present study.

Solvent-assisted chemical recycling of polycarbonate using glycerol as a renewable chemical: mechanistic insights and statistical optimization - Markandeya, Nishant; Jadhav, Mayur; Gopale, Prafulla; Ramalingam, Karthick; Kamble, Sanjay (Process Safety and Environmental Protection, 2026)
The rapid accumulation of polycarbonate (PC) waste has driven the development of efficient recycling methods. This study presents a comprehensive investigation of solvent-assisted chemical recycling of PC using glycerol, a renewable chemical derived from industrial waste streams. Solvent screening highlighted the critical influence of solvent properties such as dielectric constant, dipole moment and hydrogen-bond accepting ability on depolymerization efficiency. A systematic approach combining Design of Experiments (DoE) and Response Surface Methodology (RSM) was employed to optimize the depolymerization process. Using a Box-Behnken design (BBD), the effects of key process parameters, including temperature, reaction time and the glycerol (GLY:PC) and dimethylformamide (DMF:PC) weight ratios, were evaluated in terms of PC conversion and bisphenol A (BPA) yield. The optimization model predicted that a reaction temperature of 171 degrees C, a reaction time of 1 h and a PC: GLY:DMF ratio of 1:5.05:7.22 would yield 100 % PC conversion and 85 % BPA yield. Experimental validation under these conditions achieved 100 % PC conversion and 83 % BPA yield, confirming the reliability of the model. Product characterization using NMR, LC-HRMS and FTIR confirmed the purity of BPA and provided insights into the reaction mechanism. The solvent recyclability across successive reaction cycles demonstrated the environmental and economic viability of the process. Overall, the energy demand calculation based on the environmental energy impact factor (xi) highlights the industrial relevance of this work and demonstrate an efficient and environmentally friendly catalyst-free route for depolymerization of polycarbonate with strong potential for industrial implementation.
Keywords: Chemical Recycling; Glycerol; Polycarbonate; Response surface methodology